Encounters on contested lands : Indigenous performances of sovereignty and nationhood in Québec - Burelle, Julie (Evanston, Illinois : Northwestern University Press, 2019)
Encounters on Contested Lands analyzes films, plays, visual art, and protest marches by Indigenous artists in Quebec, Canada, to explore the performance of cultural identity, sovereignty, and nationhood in Quebec's independence movement--Provided by publisher.
Introduction: Nation, spectacle, and colliding narratives -- Neptune redux : the (First) Nation(s) enacted in Alexis Martin's Invention du chauffage central en Nouvelle-France -- Les racines imaginaires/mythical metissages : Quebec and the ruse of the metis turn -- Cinematic encounters on the reserve -- Endurance/enduring performance : Nadia Myre, La Marche Amun, and the Indian Act's tumultuous geographies -- Theater in contested lands : repatriating ancestors amid violence -- Conclusion.
Revised and expanded version of the author's thesis (doctoral)--University of California, San Diego, 2014.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 07, 2018).
eBooks on EBSCOhost
Keywords: Decolonization -- Québec (Province) -- History; Self-determination, National -- Québec (Province) -- History; Indians of North America -- Québec (Province) -- Politics and government; Indians of North America -- Québec (Province) -- Government relations; Indians of North America -- Land tenure -- Québec (Province); Indians of North America -- Rites and ceremonies -- Political aspects -- Québec (Province) -- Drama; Indians of North America -- Québec (Province) -- Ethnic identity -- Drama; Décolonisation -- Québec (Province) -- Histoire; Droit des peuples à disposer d'eux-mêmes -- Québec (Province) -- Histoire; Premières Nations -- Québec (Province) -- Relations avec l'État.; Peuples autochtones -- Terres -- Québec (Province); PERFORMING ARTS / Theater / General; PERFORMING ARTS / General; Decolonization; Indians of North America -- Ethnic identity; Indians of North America -- Government relations; Indians of North America -- Land tenure; Indians of North America -- Politics and government; Self-determination, National; Québec; Drama; History